Stability Analysis, Design, and Simulation of X band Gyro-twystron Amplifiers - Singh, Anshu Sharan (IIT(BHU) Varanasi, 2019)
Abstract is available in content.
Keywords: Design,of X band Gyro-twystron Amplifiers; Simulation of X band Gyro-twystron Amplifiers; Stability Analysis of X band Gyro-twystron Amplifiers